Measuring Poverty in Lebanon Using 2011 HBS - Lebanon Central Administration of Statistics; World Bank (World Bank, Washington, DC, 2017)
The purpose of this technical note is to describe how the welfare aggregate and poverty line were constructed in Lebanon using HBS 2011. It is a part of broader collaboration between CAS and the World Bank to improve data quality and poverty monitoring capabilities in the country. Different approaches have been tested to correct non-response and to measure poverty. The note consists of eight sections. Section 2 briefly discusses main methodological issues in poverty measurement. Section 3 explains construction of different components of welfare aggregate. Section 4 documents construction of poverty lines. Triangulation of obtained poverty estimates, sensitivity analysis are conducted in section 5. This section also contains supplementary poverty numbers based on consumption per adult equivalent. Finally, section 6 concludes and discusses areas for further consideration in poverty measurement.